Association of mental and physical health of first year undergraduate students with ABO blood groups in an Indian urban medical college - Nikam, Lalita H. (International Journal of Research in Medical Sciences, 2020)
Background: Medical students tend to have greater stress levels than the general population. Present study aims to explore mental and physical health of first year medical undergraduate students and association with different ABO blood groups. Methods: In this cross-sectional study, 99 first year students were segregated on the basis of ABO blood groups. Mental health was assessed using validated General Health Questionnaire (GHQ-12). For physical health, height and weight of each student were measured and Body Mass Index (BMI) was calculated. Results: Study shows higher prevalence of stress (GHQ-12 scores) of 54.6%. There was no statistically significant association of stress levels (GHQ-12 scores) and BMI with various ABO Blood groups using Pearson Chi Square test. On comparison GHQ-12 scores were highest for O blood group students and BMI values were greater in blood group B and O, but not significant. AB blood group had least GHQ-12 scores and BMI. On correlation of GHQ-12 scores with BMI, there was weak positive correlation. Conclusions: Blood groups have no association with mental and physical health status. Interventions in early phase to reduce stress in medical students will reduce incidence of obesity and related health disorders in future.